1994
DOI: 10.1093/hmg/3.12.2093
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal methylation pattern in constitutive and facultative (X inactive chromosome) heterochromatin of ICF patients

Abstract: We have investigated the distribution of DNA methylation in chromosomes and nuclei of normal individuals and ICF (Immunodeficiency, Centromeric instability and Facial abnormalities) syndrome patients, using 5-methylcytosine monoclonal antibody. In this syndrome, DNA digestion with methyl-sensitive enzymes has previously shown a specific hypomethylation of classical satellites located in constitutive heterochromatin. The chromosome methylation pattern confirms this hypomethylation showing in addition a clear un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
120
2

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(128 citation statements)
references
References 0 publications
6
120
2
Order By: Relevance
“…These regions are normally heavily methylated in somatic cells but ICF patients demonstrate a marked hypomethylation of these regions (Jeanpierre et al, 1993;Tagarro et al, 1994), indicating that DNA methylation may be essential for proper centromere structure and stability. Repetitive elements elsewhere in the genome, including a subtelomeric repeat (Kondo et al, 2000), and single copy sequences on the inactive X chromosome (Hansen et al, 2000;Miniou et al, 1994) have also been shown to undergo hypomethylation in ICF cells. In contrast to the drastic hypomethylation of satellite 2 and 3 sequences, overall genomic 5-methylcytosine levels in ICF versus normal lymphoblastoid cell lines (LCLs) was unchanged (a result likely in¯uenced by cell culture), and primary ICF brain tissue showed only a 7% decrease in 5-methylcytosine content (Tuck-Muller et al, 2000).…”
Section: Icf Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…These regions are normally heavily methylated in somatic cells but ICF patients demonstrate a marked hypomethylation of these regions (Jeanpierre et al, 1993;Tagarro et al, 1994), indicating that DNA methylation may be essential for proper centromere structure and stability. Repetitive elements elsewhere in the genome, including a subtelomeric repeat (Kondo et al, 2000), and single copy sequences on the inactive X chromosome (Hansen et al, 2000;Miniou et al, 1994) have also been shown to undergo hypomethylation in ICF cells. In contrast to the drastic hypomethylation of satellite 2 and 3 sequences, overall genomic 5-methylcytosine levels in ICF versus normal lymphoblastoid cell lines (LCLs) was unchanged (a result likely in¯uenced by cell culture), and primary ICF brain tissue showed only a 7% decrease in 5-methylcytosine content (Tuck-Muller et al, 2000).…”
Section: Icf Syndromementioning
confidence: 99%
“…For example, V(D)J recombination is reduced more than 100-fold when the recombination substrate is methylated (Hsieh and Lieber, 1992). In addition, Dnmt1 knockout ES cells exhibit a 10-fold increased mutation rate involving gene rearrangements (Chen et al, 1998), and individuals with ICF syndrome or cultured cells treated with 5-azaCdR show increased numbers of chromosomal translocations (Ji et al, 1997;Miniou et al, 1994).…”
Section: Dna Hypomethylation ± Roles In Cancer and Genome Stabilitymentioning
confidence: 99%
“…21,23 Although global levels of DNA methylation are only slightly reduced in ICF patients, 24 pericentromeric satellite repeat sequences on chromosomes 1, 9 and 16 are highly decondensed and hypomethylated. 15,[25][26][27][28][29] Other non-satellite repeat regions 30 and a number of genes on inactive X chromosome in female ICF patients [31][32][33][34][35] are also hypomethylated. However, in-depth genome-wide analyses of the methylation effects of DNMT3B deficiency have not been previously performed.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Somewhat analogous to tumour development models, alterations in the methylation pattern may predispose cells to chromosomal instability with abnormal changes in chromatin organization. 19 Perhaps, one of the most fascinating features of genomic hypomethylation are the changes in DNA stability and chromatin undercondensation. 20 The knockout of DNMT3b in embryonic stem cells promotes genome-wide destabilization.…”
Section: The Two Sides Of Genomic Methylationmentioning
confidence: 99%
“…17,18 Somewhat analogous to tumour development models, alterations in the methylation pattern may predispose cells to chromosomal instability with abnormal changes in chromatin organization. 19 Perhaps, one of the most fascinating features of …”
mentioning
confidence: 99%